Negotiating a place in town. Street vending in Thika (Kenya) - Nathan Mwangi Kariuki; Sylvain Racaud (EchoGéo, 2024)
This article shows how street vendors negotiate their place in the city by appropriating streets in a precarious and conflictual environment. The streets are the object of power struggles between the local authorities and the street vendors, who legitimize their presence by relying on laws and other framework texts from the central government. Two essential characteristics of public regulation are revealed: normative stacking and discordance, which produce an ambiguous institutional environment, with contradictions between acts - at the national level - and by-laws - at the local level. It is precisely these ambiguities that open up areas of conflict. There is also a gap between local or national texts and everyday practices, as illustrated by petty corruption. These « informal” trading streets showcase the confrontation between two legitimacies: that of people with low incomes rooted in the local context and that of project promoters of a globalized urban modernity. Street vending, a vulnerable activity, is a means of building identities, a social life, and a sense of belonging in the precarious environment of African cities.